2010
DOI: 10.1063/1.3486465
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathway analysis for dislocation nucleation from a sharp corner in silicon: Glide set versus shuffle set

Abstract: Using reaction pathway sampling, we have investigated the shear stress dependences of the activation energies of shuffle-set and glide-set dislocation nucleation from a sharp corner in silicon. The gradient of the glide-set dislocation curve is lower than that of the shuffle-set dislocation, and the athermal stress of glide-set dislocation is largely higher than that of shuffle-set dislocation. As a result, the two curves have a cross point, which means that shuffle-set dislocation is likely nucleated at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…Godet et al confirmed using molecular dynamics (MD) simulations that each of these two dislocation sets can be activated in Si slabs from surfaces under tension at particular conditions [14]. At high temperatures and low tensile stress nucleation of dislocations in a glide set was observed, while at low temperatures and high tensile stress shuffle dislocation nucleation was reported [15]. In a different study Godet et al examined mechanism of mechanical failure of (001) surface oriented Si nanolayer on tensile direction [8].…”
Section: Introductionmentioning
confidence: 96%
“…Godet et al confirmed using molecular dynamics (MD) simulations that each of these two dislocation sets can be activated in Si slabs from surfaces under tension at particular conditions [14]. At high temperatures and low tensile stress nucleation of dislocations in a glide set was observed, while at low temperatures and high tensile stress shuffle dislocation nucleation was reported [15]. In a different study Godet et al examined mechanism of mechanical failure of (001) surface oriented Si nanolayer on tensile direction [8].…”
Section: Introductionmentioning
confidence: 96%
“…Molecular dynamics simulation becomes capable of analyzing the activation energies of dislocation nucleation under different conditions. (11) We expect that molecular dynamics could explain the decrease in BDT temperature under a severely strained Si crystal of micron thickness in the near future. …”
Section: Discussionmentioning
confidence: 95%
“…Our view is that it is necessary to assess how experimental variables affect the above key variables in order to formulate a DBT model that does not depend on empirical constants. This requires understanding of how confining pressure, 205 radiation enhanced dislocation glide (REDG), 206 impurities, 207 state of stress, 208 and length scale 209 affect dislocation nucleation and mobility. The REDG effect 204 is important since most studies of length scale effects at submicron sizes are accomplished in either SEM or TEM.…”
Section: Future Nanomechanical Approaches To Brittleness Transitionsmentioning
confidence: 99%